Measurement of the differential cross sections of 6,7Li(d,d0)6,7Li for Ion Beam Analysis purposes - Ntemou, E.; Aslanoglou, X.; Axiotis, M.; Foteinou, V.; Kokkoris, M.; Lagoyannis, A.; Misaelides, P.; Patronis, N.; Preketes-Sigalas, K.; Provatas, G.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
N/A